Participatory Flood Risk Mapping Using the Geographic Information System (DIG-GIS) Integration in Beru-Beru Village, Mamuju Regency - Rafid Mahful; windy septia sintia; zul asriana; Muh. Rafli Ar Rasyid; amirul asnan; Ummu Kalsum Basman; Ellyni Dwi Fortuna; Eliana Eliana; Aldidayansyah Aldidayansyah; Dedi Setyadi; Hardiansyah Hardiansyah (Journal of Architectural Design and Urbanism, 2025)
Recurring floods in Beru-Beru Village, West Sulawesi, devastate 200 hectares annually, resulting in economic losses of Rp 2 billion. This study presents a participatory approach that combines Geographic Information Systems (GIS) with Disaster Imagination Games (DIG) to transform community-based flood risk assessment. Utilizing structured stakeholder engagement with 40 people, we employed the risk formula R = (H × V × (1-C))¹/² on 1,401.2 hectares, uncovering significant regional variation. 15.4% of high-risk areas are centered in the Kampung Baru and Kampung Rea hamlets, whilst 30.1% of the region exhibited very low adaptive capacity. The incorporation of DIG-GIS facilitated unparalleled community engagement, converting passive risk recipients into proactive risk evaluators, hence allowing for real-time verification of technical studies through the amalgamation of local expertise. This methodology, in contrast to traditional top-down approaches, attained 89% stakeholder consensus in risk prioritization and enhanced hazard awareness by 340% relative to the first survey. This framework's primary novelty is the democratization of scientific risk assessment, coupled with technical rigor, resulting in spatially explicit risk maps that are comprehensible and trusted by the community. Research findings demonstrate that participatory GIS, when integrated with serious games, can effectively connect expert knowledge with community perceptions, fundamentally shifting catastrophe planning from a reactive to a proactive framework. This methodological advancement provides a quantifiable option for flood-prone developing areas where community endorsement is crucial for the efficacy of interventions.